Determinan Pengungkapan Enterprise Risk Management Terhadap Perusahaan Perbankan di Indonesia - Abdul Rohman Wahit Arief; Muhammad Mansur; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to obtain empirical evidence of the influence of company size, leverage, ownership concentration, auditor reputation, and chief risk officer on disclosure of Enterprise Risk Management. The population in this study is banking companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique is done by using purposive sampling method which produces 37 samples in 2016-2018. The data used are secondary data taken through documentation techniques which consist of annual reports of banking companies in 2016-2018. Data analysis method in this research is multiple linear regression analysis. This study proves that company size, leverage, ownership concentration, auditor reputation, and chief risk officer simultaneously have a positive effect on disclosure of Enterprise Risk Management. Partial testing shows that company size and leverage have no significant effect on disclosure of Enterprise Risk Management. The concentration of ownership, auditor's reputation, and chief risk officer significantly influences the disclosure of Enterprise Risk Management. Keywords: company size, leverage, ownership concentration, auditor reputation, and chief risk officer.